Gender segregation in the engineering and science professions : a case of continuity and change - Devine, Fiona [Verfasser] (My University, 1992)
"It has been argued that gender segregation may be declining or, at least, that more complex and subtle forms of gender segregation are now discernible as women acquire the necessary educational credentials to enter previously maledominated professional occupations. Drawing on a case study of engineering and science, it will be seen that the 'gendered' nature of subject choices in the educational system accounts for the persistence of gender segregation in the technical professions. Moreover, despite the introduction of equal opportunity legislation, the small number of women acquiring technical degrees still face discrimination from hostile managers in the reccruitment process, and childcare and domestic responsibilities continue to block their occupational mobility within organisations where uninterrupted linear careers are the norm. The 'liberal feminist' strategy of acquiring the necessary 'human capital' to undermine social closure, in other words, has not substuntially reduced horizontal and vertical gender segregation in technical professions historically almost exclusively dominated by men." (author's abstract) ((en)) Im Rahmen einer betrieblichen Fallstudie wird der Frage nachgegangen, ob die geschlechtsspezifische Segregation des Arbeitsmarktes für Technikerinnen durch die verbesserte Ausbildung von Frauen in Grossbritannien aufgeweicht wurde. Es zeigt sich, dass zum einen die geschlechtsspezifische Berufswahl, aber auch das Einstellungsverhalten der Personalchefs zu einer fortbestehenden Segregation beitragen. (IAB)
Geschlechtersegregation bei Ingenieuren und wissenschaftlichen Berufen - Ein Fall von Kontinuität und Wandel
Keywords: S 6.3.1 Ingenieurberufe, Chemiker, Physiker, Mathematiker; G 2.4.5 Gender Mainstreaming; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; P 1.3 Frauen; G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; Arbeitsmarkt; Segregation; Geschlechtsspezifische Faktoren; Techniker; Ingenieur; Gleichstellungspolitik; Effizienz; Hochqualifizierter; Frauen in Einzelberufen; Frauenarbeit; Kinderbetreuung; Berufsproblem; Personalgewinnung; Berufsverlauf; Ausgrenzung; Berufswahl